2021
DOI: 10.1038/s41598-021-97411-3
|View full text |Cite
|
Sign up to set email alerts
|

First report of Borrelia burgdorferi sensu stricto detection in a commune genospecies in Apodemus agrarius in Gwangju, South Korea

Abstract: Lyme disease is a tick-borne infectious disease caused by the Borrelia burgdorferi sensu lato complex. However, the distribution of Borrelia genospecies and the tissue detection rate of Borrelia in wild rodents have rarely been investigated. Here, we studied 27 wild rodents (Apodemus agrarius) captured in October and November 2016 in Gwangju, South Korea, and performed nested polymerase chain reaction targeting pyrG and ospA to confirm Borrelia infection. Eight rodents (29.6%) tested positive for Borrelia infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In this study, only B. afzelii was detected, but previous studies confirmed B. garinii, which is known to be pathogenic to humans, similar to B. afzelii. A recent study in which B. afzelii and B. garinii was detected in wild rodent tissues showed that the Borrelia-positive rate was 29.8% and 25.9% for B. afzelii and 3.7% for B. garinii [10]. Another study identified Borrelia genospecies in various sampling areas in Korea, which were identified as B. afzelii (62.5%) and B. garinii (1.6%) [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, only B. afzelii was detected, but previous studies confirmed B. garinii, which is known to be pathogenic to humans, similar to B. afzelii. A recent study in which B. afzelii and B. garinii was detected in wild rodent tissues showed that the Borrelia-positive rate was 29.8% and 25.9% for B. afzelii and 3.7% for B. garinii [10]. Another study identified Borrelia genospecies in various sampling areas in Korea, which were identified as B. afzelii (62.5%) and B. garinii (1.6%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence has increased since then [4,7]. In Korea, on average, 15.4 cases per year have been reported in the past decade, with 23 cases reported in 2019 and 18 cases reported in 2020 [9,10]. In Korea, research on Borrelia is currently being carried out on the pathogenicity of various wild animals, including ticks, rodents, and companion animals [3,7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water deer (Hydropotes inermis Swinho, 1870) comprise two subspecies: H. inermis inermis in the eastern region of China and H. inermis argyropus across South Korea, listed as vulnerable on the International Union for Conservation of Nature (IUCN) Red List [19]. In China, H. inermis inermis faces declining numbers due to habitat loss and fragmentation, whereas H. inermis argyropus thrives throughout South Korea, where its ecosystem lacks natural predators [20][21][22][23]. A generalist species, water deer adeptly inhabit croplands, wetlands, grasslands, and forests [23], displaying edge species characteristics [19].…”
Section: Introductionmentioning
confidence: 99%
“…burgdorferi s.l. was first detected in 1993 and has been sporadically identified in ticks, dogs, horses, wild rodents, and humans [ 51 56 ].…”
Section: Introductionmentioning
confidence: 99%